1983
DOI: 10.1037/0022-3514.44.4.798
|View full text |Cite
|
Sign up to set email alerts
|

Social confirmation of dysphoria: Shared and private reactions to depression.

Abstract: Social responses to dysphoria were investigated. Subjects conversed for 15 minutes with persons selected on the basis of the presence or absence of depressed mood. Following the conversations, mood measures were administered along with social perception questionnaires that were described as either being confidential or to be shared with the other person. Subjects who interacted with depressed persons were anxious, depressed, and hostile, and the subjects rejected them. Contrary to predictions, subjects were wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
166
4

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(181 citation statements)
references
References 19 publications
11
166
4
Order By: Relevance
“…Coyne, Burchill, & Stiles, 1991;Strack & Coyne, 1983). However, it is argued here that this response to depressed individuals depends in part on how the target copes with his or her depression.…”
mentioning
confidence: 87%
“…Coyne, Burchill, & Stiles, 1991;Strack & Coyne, 1983). However, it is argued here that this response to depressed individuals depends in part on how the target copes with his or her depression.…”
mentioning
confidence: 87%
“…A fourth study (Gibbons, 1986) found that following a worsening of their moods, depressed college students preferred to read descriptions of life events written by individuals also experiencing negative moods. Finally, in a study involving actual face-toface interactions, Strack and Coyne (1983) found that depressed subjects were less interested than nondepressed subjects in future interactions with a nondepressed partner. This study did not examine the reactions of depressed subjects to a depressed partner.…”
mentioning
confidence: 99%
“…Two studies compared nondepressed students interacting face-to-face with depressed or nondepressed students in a 15-min "get acquainted" conversation (Gotlib & Robinson, 1982;Strack & Coyne, 1983). One found that the nondepressed subjects who had talked with depressed people came to feel more hostile, depressed, anxious, and less willing to interact with their partner in the future (Strack & Coync, 1983).…”
mentioning
confidence: 99%
“…This is shown in the bottom HD chart of Figure D-3 where the HD goes to zero. Strack and Coyne (1983) found that happy people working with depressed or sad people tended to become sad very quickly. Gotlieb and Robinson (1982) had similar results.…”
Section: D2245 Co-evolutionmentioning
confidence: 99%